High Latitude Epipelagic and Mesopelagic Scattering Layers—A Reference for Future Arctic Ecosystem Change - Knutsen, Tor; Wiebe, Peter H.; Gjøsæter, Harald; Ingvaldsen, Randi B.; Lien, Gunnar (Frontiers in Marine Science, 2017)
Scattering structures, including deep (>200 m) scattering layers are common in most oceans, but have not previously been properly documented in the Arctic Ocean. In this work, we combine acoustic data for distribution and abundance estimation of zooplankton and fish with biological sampling from the region west and north of Svalbard, to examine high latitude meso- and epipelagic scattering layers and their biological constituents. Our results show that typically, there was strong patchy scattering in the upper part of the epipelagic zone (<50 m) throughout the area. It was mainly dominated by copepods, krill, and amphipods in addition to 0-group fish that were particularly abundant west of the Spitsbergen Archipelago. Off-shelf there was a distinct deep scattering layer (DSL) between 250 and 600 m containing a range of larger longer lived organisms (mesopelagic fish and macrozooplankton). In eastern Fram Strait, the DSL also included and was in fact dominated by larger fish close to the shelf/slope break that were associated with Warm Atlantic Water moving north towards the Arctic Ocean, but switched to dominance by species having weaker scattering signatures further offshore. The Weighted Mean Depths of the DSL were deeper (WMD >440 m) in the Arctic habitat north of Svalbard compared to those south in the Fram Strait west of Svalbard (WMD ~400 m). The surface integrated backscatter (Nautical Area-Scattering Coefficient, NASC, sA [m2∙nmi-2]) was considerably lower in the waters around Svalbard compared to the more southern regions (62-69ºN). Also, the mesopelagic nautical area scattering coefficient was a factor of approximately 6-10 lower around Svalbard compared to the areas in the south-eastern part of the Norwegian Sea ~62º30’N. The documented patterns and structures, particularly the DSL and its constituents, will be key reference points for understanding and quantifying future changes in the pelagic ecosystem at the entrance to the Arctic Ocean.